2019
DOI: 10.1126/sciadv.aax5733
|View full text |Cite
|
Sign up to set email alerts
|

Electric dipole effect in PdCoO 2 /β-Ga 2 O 3 Schottky diodes for high-temperature operation

Abstract: High-temperature operation of semiconductor devices is widely demanded for switching/sensing purposes in automobiles, plants, and aerospace applications. As alternatives to conventional Si-based Schottky diodes usable only at 200°C or less, Schottky interfaces based on wide-bandgap semiconductors have been extensively studied to realize a large Schottky barrier height that makes high-temperature operation possible. Here, we report a unique crystalline Schottky interface composed of a wide-gap semiconductor β-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…Until recent years, β-Ga 2 O 3 has been attracting quite an attention from researchers, due to its promising semiconducting properties: temperature stability, optical transparencies, or photostability due to large energy bandgap, high breakdown electric (E)-field, and minimum leakage current. [1][2][3][4][5][6][7][8][9] Gallium trioxide is basically known to have five different polymorphisms, α, β, γ, δ, and ε. [10,11] Of these modifications monoclinic β-Ga 2 O 3 is the most stable form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recent years, β-Ga 2 O 3 has been attracting quite an attention from researchers, due to its promising semiconducting properties: temperature stability, optical transparencies, or photostability due to large energy bandgap, high breakdown electric (E)-field, and minimum leakage current. [1][2][3][4][5][6][7][8][9] Gallium trioxide is basically known to have five different polymorphisms, α, β, γ, δ, and ε. [10,11] Of these modifications monoclinic β-Ga 2 O 3 is the most stable form.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] Likewise, pure vdW junction between metallic TMDs and β-Ga 2 O 3 seems unlikely in the present study. Figure 1b [36][37][38] Atomic force microscopy (AFM) to measure thickness of Nb(Ta)S 2 and β-Ga 2 O 3 has been conducted with MESFET structure, and exemplary 3D thickness profiles are thus shown in Figure 1c,d in literature (qΦ W of NbS 2 , [39,40] TaS 2 , [39,41] and β-Ga 2 O 3 [2,3] ≈6.0, ≈5.6, and ≈4.1 eV, respectively). Such difference is attributed to possible existence of ultrathin oxide (NbO x or TaO x ) on TaS 2 or NbS 2 , since those TMDs are so weak to oxidation in air ambient.…”
Section: Introductionmentioning
confidence: 99%
“…Delafossite structured ternary oxides and nitrides have always attracted great interests in fundamental sciences and technological applications during the past decades. [ 1–5 ] Specifically, metallic delafossite oxides (ABO 2 ), such as PdCrO 2 , PdCoO 2 , and PtCoO 2 showing extraordinarily high conductivity, have been adopted as a new benchmark for conductive oxides. [ 1 ] Delafossite ABO 2 has a natural superlattice‐like structure composed of alternatively stacked noble‐metal A‐atoms and edge‐sharing BO 6 oxygen octahedra with linear OAO ionic bonds to interlink the sublayers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PdCoO 2 thin films have been successfully synthesized by molecular beam epitaxy (MBE) and pulsed laser deposition (PLD). [ 2,15–17 ] Specifically, Brahlek et al systematically investigated the growth of high‐quality epitaxial PdCoO 2 thin films (10 × 10 cm 2 ) by MBE, where the room temperature conductivity has reached as high as 2.6 × 10 5 S cm −1 for a 125 nm‐thick thin film annealed in oxygen. [ 17 ] It is suggested that metallic ABO 2 thin films can be potential utilized for various electronic devices ranging from low‐resistivity bottom electrodes for 2D materials to correlated transparent conductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation